Urinary N-acetyl-β-D glucosaminidase as a surrogate marker for renal function in autosomal dominant polycystic kidney disease: 1 year prospective cohort study - Park Hayne; Hwang Jin; Kang Ah-Young; Ro Han; Kim Myung-Gyu; An Jung; In Park Ji; Kim Seung; Yang Jaeseok; Oh Yun; Oh Kook-Hwan; Noh Jung; et al. (BMC Nephrology, 2012)
Abstract Background Renal failure is one of the most serious complications associated with autosomal dominant polycystic kidney disease (ADPKD). To date, early markers have failed to predict renal function deterioration at the early stages. This 1-year prospective study evaluated N-acetyl-β-D-glucosaminidase (NAG) as a new surrogate marker for renal function in ADPKD. Methods A total of 270 patients were enrolled in the study, and we measured urinary NAG, β2-microglobulin, neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) prospectively for 1 year to compare their predictive values for renal function. Results Baseline urinary NAG/Cr was negatively correlated with estimated glomerular filtration rate (GFR) (r2 = 0.153, P < 0.001) and positively correlated with total kidney volume (TKV) (r2 = 0.113, P < 0.001). Among other biomarkers, urinary NAG/Cr better discriminated patients with decreased renal function from those with conserved renal function, showing the largest area under the curve (AUC 0.794). Immunohistochemical study revealed strong staining along the cyst-lining epithelial cells as well as the nearby compressed tubular epithelial cells. However, both single and repeated measurements of urinary NAG/Cr failed to predict renal function decline in 1 year. Conclusions Urinary NAG/Cr may be a useful surrogate marker for renal function in ADPKD patients.